Meaning in Life and Self-Control Buffer Stress in Times of COVID-19: Moderating and Mediating Effects With Regard to Mental Distress - Schnell, Tatjana; Krampe, Henning (Frontiers in Psychiatry, 2020)
Background: Mental distress increased substantially during the COVID-19 pandemic. Citizens had to exercise a high degree of self-control. We also witnessed an increase of prosocial acts and creative expressions, known to serve as sources of meaning. Meaningfulness and self-control are acknowledged psychological resources in times of crisis. The present study documents levels of acute COVID-19 stress and general mental distress in Germany and Austria during the lockdown and the weeks thereafter. We examined buffering effects of meaningfulness and self-control and a potential aggravation of mental distress due to crises of meaning, as well as potential risk factors for COVID-19 stress. Method: A cross-sectional survey was conducted during lockdown and the subsequent weeks. A total of N=1,538 participants completed measures of COVID-19 stress, meaningfulness and crisis of meaning (SoMe), self-control (SCS-KD), and general mental distress (PHQ-4). First, associations between living conditions, demographics, and COVID-19 stress were explored. Second, a double moderation and a dual moderated mediation model were tested. Results: We found higher COVID-19 stress during lockdown than in the weeks thereafter, while the rate of severe general mental distress and crises of meaning was substantially elevated in the weeks following the lockdown. COVID-19 stress and general mental distress were strongly related (r = .53). Both meaningfulness and self-control moderated the relationship between COVID-19 stress and PHQ-4, and crisis of meaning mediated it. Survey group moderated the first path of this mediation, i.e. the relationship between COVID-19 stress and crisis of meaning; self-control moderated the second path, i.e. the relationship between crisis of meaning and PHQ-4. Discussion: Elevated PHQ-4 scores indicated an ongoing destabilization. Meaningfulness and self-control were related to lower mental distress and also served as buffers: When COVID-19 stress was high, meaningfulness and self-control accounted for lower PHQ-4 scores. High COVID-19 stress was additionally linked to crises of meaning which were associated with mental distress. Public health policies can support citizens by enabling experiences of meaningfulness, e.g. through transparent and comprehensive modes of communicating goals and intermediate steps. Self-control can be boosted by keeping higher-order goals salient—which is inherently linked to an understanding of their meaning.